The Power of Plants: Is a Whole-Foods, Plant-Based Diet the Answer to Health, Health Care, and Physician Wellness? - Ha, Benjamin (Perm J, 2019)
The exponential rise in the cost of health care since the 1980s in the US is unsustainable. It is estimated that more than 70% of health care dollars are spent addressing the result of unhealthy lifestyles that are increasing the rates of obesity, diabetes, and cardiovascular disease. There is also a severe and worsening epidemic of physician burnout in the US, which threatens the health of physicians and patients alike. In this article, I share why I believe a whole-foods, plant-based diet is a powerful prescription for optimal health and the answer to health, health care, and physician wellness.